2004
DOI: 10.1111/j.1365-2958.2004.04213.x
|View full text |Cite
|
Sign up to set email alerts
|

Repression of the RcsC‐YojN‐RcsB phosphorelay by the IgaA protein is a requisite for Salmonella virulence

Abstract: SummaryBacterial pathogenesis relies on regulators that activate virulence genes. Some of them act, in addition, as repressors of specific genes. Intracellular-growthattenuator-A (IgaA) is a Salmonella enterica membrane protein that prevents overactivation of the RcsC-YojN-RcsB regulatory system. This negative control is critical for growth because disruption of the igaA gene is only possible in rcsC , yojN or rcsB strains. In this work, we examined the contribution of this regulatory circuit to virulence. Via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
151
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(164 citation statements)
references
References 49 publications
12
151
1
Order By: Relevance
“…Spontaneous mutations consisting of deletions leading to a diminished production of RcsC or RcsD are also known to suppress IgaA essentiality (42). Important traits of serovar Typhimurium, such as its virulence potential, depend on the fine-tuning of the activity of the RcsCDB system (17,28,45). IgaA and the RcsCDB system are present in the same genera of enteric bacteria (17,20,34), and this concurrence strongly supports the functional link existing between IgaA and the RcsCDB system.…”
mentioning
confidence: 80%
See 3 more Smart Citations
“…Spontaneous mutations consisting of deletions leading to a diminished production of RcsC or RcsD are also known to suppress IgaA essentiality (42). Important traits of serovar Typhimurium, such as its virulence potential, depend on the fine-tuning of the activity of the RcsCDB system (17,28,45). IgaA and the RcsCDB system are present in the same genera of enteric bacteria (17,20,34), and this concurrence strongly supports the functional link existing between IgaA and the RcsCDB system.…”
mentioning
confidence: 80%
“…In serovar Typhimurium, 26 RcsB-dependent but RcsA-independent genes were reported upon exposure of bacteria to sublethal concentrations of antimicrobial peptides (20). Recent studies performed with serovar Typhimurium expressing IgaA(T191P), a variant previously shown by us to be unable to repress the RcsCDB system (17), revealed that one-fifth of the genes analyzed displayed expression changes higher than twofold (55).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…There is another cytoplasmic membrane protein YrfF likely to regulate the system negatively: its homolog in Salmonella enterica, IgaA, was reported to repress the Rcs activity (Cano et al, 2002). The repression by Salmonella IgaA is crucial for the virulence of this intracellular pathogen (Domínguez-Bernal et al, 2004). In Legionella dumoffii DjlA is required for intracellular growth (Ohnishi et al, 2004), which may be because of its negative regulatory function on the Rcs system.…”
mentioning
confidence: 99%